2021
DOI: 10.1007/s11104-021-04917-w
|View full text |Cite
|
Sign up to set email alerts
|

Pearl millet genotype impacts microbial diversity and enzymatic activities in relation to root-adhering soil aggregation

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 94 publications
2
23
0
Order By: Relevance
“…Since it is related to exudates produced by roots and associated microflora, and given its key role in root physiology, the rhizosheath may be considered as a plant-related trait [20]. It is affected by plant species [23,24] and variety [19,25]. In wheat varietal differences have been shown [19] but the production of rhizosheath in ancient wheats has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is related to exudates produced by roots and associated microflora, and given its key role in root physiology, the rhizosheath may be considered as a plant-related trait [20]. It is affected by plant species [23,24] and variety [19,25]. In wheat varietal differences have been shown [19] but the production of rhizosheath in ancient wheats has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we reported a remarkable genotypic variability for root-adhering soil aggregation in pearl millet 33 . Moreover, this variability was associated with changes in rhizosphere microbiota structure and function 33 , 34 .…”
Section: Introductionmentioning
confidence: 84%
“…In previous studies, we reported a remarkable genotypic variability for root-adhering soil aggregation in pearl millet 33 . Moreover, this variability was associated with changes in rhizosphere microbiota structure and function 33 , 34 . Here, we analysed the relative contribution of root architectural characteristics and root colonization by AMF on root-adhering soil aggregation in pearl millet.…”
Section: Introductionmentioning
confidence: 84%
“…M. S. Ndour et al, 2021) even if it seems to be under complex genetic control in pearl millet (de la Fuente Canto et al, submitted). As rhizosheath formation is positively correlated with root hair length in wheat and barley, QTLs increasing root hair length and/or density to improve P capture could also indirectly improve rhizosheath formation (Delhaize et al, 2015;George et al, 2014).…”
Section: Case Study 1: Improving Phosphorus Acquisition Efficiency In...mentioning
confidence: 99%
“…First described in desert grasses, rhizosheath formation has since been reported in many cereal crops including sorghum and pearl millet (Brown et al, 2017; Duell & Peacock, 1985⁠; P. M. S. Ndour et al, 2017)⁠.⁠⁠ A positive impact of the rhizosheath on water and mineral nutrition was reported for several plants in laboratory conditions and could be partly explained by improved contact between the soil and the root surface (P. M. S. Ndour et al, 2020)⁠⁠. Phenotyping for rhizosheath size is high throughput and this trait is largely under plant genetic control and large variability exists in the germplasm in pearl millet thus making it a potential target for breeding (P. M. S. Ndour et al, 2021)⁠ even if it seems to be under complex genetic control in pearl millet (de la Fuente Canto et al, submitted)⁠. As rhizosheath formation is positively correlated with root hair length in wheat and barley, QTLs increasing root hair length and/or density to improve P capture could also indirectly improve rhizosheath formation (Delhaize et al, 2015; George et al, 2014)⁠.⁠ However, rhizosheath formation could represent a significant carbon sink, and further work is needed to demonstrate the impact of a larger rhizosheath on dryland cereals in West African field conditions.…”
Section: Case Study 2: Improving Water and Nutrient Acquisition In Dr...mentioning
confidence: 99%